Women (Do Not) Belong Here: Gender-Work Identity Conflict among Female Police Officers - Veldman, Jenny; Meeussen, Loes; Van Laar, Colette; Phalet, Karen (Frontiers in Psychology, 2017)
The current paper examines antecedents and consequences of perceiving conflict between gender and work identities in male-dominated professions. In a study among 657 employees working in 85 teams in the police force, we investigated the effect of being different from team members in terms of gender on employees’ perception that their team members see their gender identity as conflicting with their work identity. As expected in the police force as a male-dominated field, the results showed that gender-dissimilarity in the team was related to perceived gender-work identity conflict for women, and not for men. In turn, perceiving gender-work identity conflict was related to lower team identification for men and women. Although lowering team identification might enable employees to cope with conflicting social identities and hence protect the self, this may also have its costs, as lower team identification predicted higher turnover intentions, more burn-out symptoms, less extra role behavior, lower job satisfaction, lower work motivation, and lower perceived performance. Additionally, for women, experiencing support from their team members and team leader showed a trend to mitigate the relationship between gender-dissimilarity and perceived gender-work identity conflict, and a positive diversity climate was marginally related to less perceived gender-work identity conflict. The results show the importance of the team context in shaping a climate of (in)compatible identities for numerically underrepresented and historically undervalued social group members in order to hinder or protect their work outcomes.